The Role of Weather during the Greek–Persian “Naval Battle of Salamis” in 480 B.C. - Christos Zerefos (Atmosphere, 2020)
The Battle of Salamis in 480 B.C. is one of the most important naval battles of all times. This work examines in detail the climatically prevailing weather conditions during the Persian invasion in Greece. We perform a climatological analysis of the wind regime in the narrow straits of Salamis, where this historic battle took place, based on available station measurements, reanalysis and modeling simulations (ERA5, WRF) spanning through the period of 1960–2019. Our results are compared to ancient sources before and during the course of the conflict and can be summarized as follows: (i) Our climatological station measurements and model runs describing the prevailing winds in the area of interest are consistent with the eyewitness descriptions reported by ancient historians and (ii) The ancient Greeks and particularly Themistocles must have been aware of the local wind climatology since their strategic plan was carefully designed and implemented to take advantage of the diurnal wind variation. The combination of northwest wind during the night and early morning, converging with a south sea breeze after 10:00 A.M., formed a “pincer” that aided the Greeks at the beginning of the clash in the morning, while it brought turmoil to the Persian fleet and prevented them to escape to the open sea in the early afternoon hours.